INVESTIGATION ON YOUNG ADULT HAND GRIP STRENGTH - Nor Julahah J; Ummi Noor Nazahiah A; M. Asyraf CD; Norashiken O; Ahmad Faizal Salleh (Malaysian Journal of Public Health Medicine, 2020)
It is believed that exposure to whole-body vibration (WBV) may increase seated occupant drowsiness and seated. The purpose of this paper is to investigate the strength of the hand grip among the young adults in Malaysia. Also, to examine the correlation between anthropometry factors such as hand length (HL), hand breadth (HB), wrist circumference (WC) and body mass index (BMI) with average full hand grip strength of young adults. 40 Malaysian young adults with equal females and males and the range age of 23 to 28 years old voluntarily basis participated in this study. Three experiments were conducted in sitting position according to American Standard Hand Therapist (ASHT) with 45º, 90o and 135o of hand flexion using dynamometer. The results show the significant different full hand grip strength between Malaysian young adult females and females, the difference full hand grip strength for different hand flexion angles in sitting position and difference correlations between anthropometry factors and full hand grip strength for both young adult males and females.